2002
DOI: 10.1038/sj.ijo.0802010
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin concentration in obese patients with binge eating disorder

Abstract: BACKGROUND:In steady-state conditions serum leptin concentration is directly related to body fat stores, but is also affected by changes in energy balance. This cross-sectional study investigated the serum leptin concentrations of severely obese patients with binge eating disorder (BED), in whom body fat was greater than normal and, because of eating pattern, rapid and repeated changes in energy balances took place. METHODS: A group of BED obese patients was compared to a group of obese patients with a regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
2
20
0
11
Order By: Relevance
“…In BN individuals, instead, the circulating levels of either AEA or 2-AG did not significantly differ from control women. Moreover, as previously reported by both our group and other authors (Monteleone et al, 2002a, b;Adami et al, 2002), circulating leptin levels were drastically reduced in AN patients and significantly increased in BED individuals, but did not significantly change in BN women. The most likely hypothesis accounting for similar changes of circulating AEA in individuals who are at the opposite of the ED spectrum is provided by the observed changes in leptin signalling.…”
Section: Discussionsupporting
confidence: 90%
“…In BN individuals, instead, the circulating levels of either AEA or 2-AG did not significantly differ from control women. Moreover, as previously reported by both our group and other authors (Monteleone et al, 2002a, b;Adami et al, 2002), circulating leptin levels were drastically reduced in AN patients and significantly increased in BED individuals, but did not significantly change in BN women. The most likely hypothesis accounting for similar changes of circulating AEA in individuals who are at the opposite of the ED spectrum is provided by the observed changes in leptin signalling.…”
Section: Discussionsupporting
confidence: 90%
“…In a cross-sectional study conducted by a group of researchers at the University of Genova, in Italy, the results were like ours. They showed that obese BED patients have higher concentrations of serum leptin than non-binging counterparts and attributed such founds to body fat size and the influence of eating behavior [26].…”
Section: Resultsmentioning
confidence: 99%
“…Entre os fatores comportamentais envolvidos na SCN, destacam-se: o horário do consumo de energia; os níveis de humor durante o tempo em que estão acordados; e a frequên-cia de acordar durante a noite [23][24][25] .…”
Section: Medline Pubmedunclassified
“…Alguns estudos têm relatado aumento da concentração de leptina em pacientes obesos com TCAP, sugerindo que a leptina pode ser um sensível marcador metabólico das mudanças ocorridas na compulsão alimentar e que o aumento dos níveis dessa adipocina pode estar envolvido no desenvolvimento e/ou manutenção do comportamento compulsivo 24,25 . Estudo com 30 mulheres obesas (TCAP e não TCAP), com o objetivo de avaliar concentrações de leptina e correlacionar dados e atitudes alimentares, demonstrou relação positiva entre aumento dos níveis desta com gordura corporal e padrões alimentares, infl uenciando a frequência de compulsões alimentares, aumento de energia ingerida e tecido adiposo 25 .…”
Section: Transtorno Da Compulsão Alimentar Periódicaunclassified
See 1 more Smart Citation